Assessment of Microalgal Biodiversity as Bioindicator of Aquatic Ecosystem Health in Kombal Bay, Lombok Island, Indonesia - Jayanti*, Ervina Titi; Purwati, Nining; Ihsan, Muhsinul (Jurnal IPA & Pembelajaran IPA, 2025)
A good aquatic environment will ensure the availability of clean water, prevent the spread of disease, and support the balance of marine and freshwater ecosystems. Determination of the health status of aquatic environments can use various chemical, physical, and biological parameters. Microalgae are commonly used as bioindicators of changes in the environmental quality of aquatic ecosystems because they have high sensitivity to chemical and physical changes that enter the water. One of the areas with high ecological and economic potential in Indonesia is Kombal Bay, located on Lombok Island, West Nusa Tenggara. This study aims to determine the health level of the Kombal Bay freshwater ecosystem using microalgae as bioindicators. This study is a descriptive exploratory study with qualitative and quantitative approaches. Microalgae determination uses the Algaebase online database guide, diversity analysis uses the Shannon-Wiener diversity index (H) and the evenness index (E). The results showed that there were 23 types of microalgae, the majority of which were members of Bacillariophyta, the diversity of the microalgae community was classified as moderate (H=1.37) with an uneven distribution of species (E=0.43). The combination of these various parameters indicates that the waters of Kombal Bay are lightly to moderately polluted and are starting to show ecological pressure